Synthesis, structure-activity relationship and solubility profiling of antimycobacterial aminoquinazolinones - Akester, Jessica Nicole (Department of Chemistry, 2017)
Tuberculosis (TB) is a communicable disease caused by an infectious bacterial pathogen called Mycobacterium tuberculosis (Mtb), which is acquired through the inhalation of bacilli-containing droplets. With the emergence of resistant strains (multidrug-resistant TB (MDR-TB), extensively drug-resistant TB (XDR-TB) and totally drug-resistant TB (TDR-TB)), co-infection with human immunodeficiency virus (HIV), the existence of latent TB infection (LTBI) and the extensive treatment regimen resulting in poor patient compliance, there is therefore a need to develop novel antimycobacterial agents to address these limitations. Within this context, 2-aminoquinazolinone compounds with potent antimycobacterial activity were previously identified. Poor solubility was recognized as a major issue requiring improvement. To this end, structure-activity relationship (SAR) studies were performed around the 2-aminoquinazolinone core in order to optimize these potential antimycobacterial agents with respect to solubility and potency. Various structural modification strategies aimed at improving solubility were explored. These included reducing lipophilicity by introduction of hydrophilic substituents as well as disruption of molecular planarity and/or symmetry of the molecule through removal of aromaticity or increase in the dihedral angle. Several analogues displayed promising in vitro antimycobacterial activity against the H37Rv strain of Mtb in glycerol-containing media along with high microsomal metabolic stability. However, the same compounds, with the exception of one phenolic intermediate, were inactive in subsequent assay media that did not contain glycerol as a carbon source. On this basis, the mechanism of action of the 2-aminoquinazolinone series was postulated to be glycerol-dependent. On the other hand, structural modifications, guided by solubility-enhancing strategies, generally resulted in compounds with markedly improved solubility. Saturated ring analogues displayed the most improvement in solubility, which was also reflected in the lower melting points. Additionally, the relationships between solubility and physicochemical parameters (ClogP, tPSA and melting point) were deduced. Melting point was found to be the most strongly correlated with aqueous solubility.